Perspektif M. Fethullah Gulen tentang Golden Generation dan Relevansinya dengan Pendidikan Islam di Indonesia - Imam, Hairul (MarÃƒÂ¢ji`: Jurnal Ilmu Keislaman, 2016)
The article seeks to discuss the concept of education based on âthe Golden Generationâ promulgated by M. Fethullah Gulen in creating the best next generation. The study shows us that education is undisputedly the sole pivotal way to nurture the noble values of humanism upon the pupils. Gulenâs Golden Generation is a pure generation which is able to put themselves as an example and possess great motivation to the values of humanism to serve other people. The aim of the creation of the Golden Generation is to generate welfare for every nation and light its way to reach both physical and spiritual wellbeing. At this point, a school can be regarded as a laboratory, which offers âan efficacious medicineâ to heal social pathos and those who possess knowledge and wisdom to formulate such medicine are teachers. Family, on the other side, plays indubitably important role to support and motivate the children to develop their abilities and skills for the sake of themselves and other people. In this context, family along with society also take a pivotal part to establish what so-called âa new strong pillarâ for the nation.